Investigating the influence of Asian cultural value and financial knowledge on investment behaviours - Nga, Joyce Koe Hwee * (MAJCAFE, 2020)
This study showed the combination of composite Asian cultural value (ACV), kiasuism (“fear of loss”), and the often-associated self-esteem, social intelligence, and achievement orientation exerted an impact on investment decision-making. It further explored the mediating influence of financial knowledge on investing behaviours (namely rational, risk aversion, herding and diversification). This research is novel as it addresses a gap in behavioural research particularly on the influence on ACVs and investing decision-making.In terms of research design, this study employed a purposive sampling method engaging with 463 respondents within the Klang Valley, Malaysia. A voluntary and anonymous quantitative questionnaire utilising a 7-point Likert-like scale was employed to measure the constructs. Due to the exploratory nature and formative constructs used in this study, the PLS-SEM method was implemented to assess the model validity and test the hypotheses. The findings thus showed that kiasu values promoted herding behaviour among investors. Besides, financial knowledge acquisition was a mediator between kiasu positive behaviours and rational investing, risk aversion, and diversification. Accordingly, the study offers suggestions of importance for financial planners, especially in Malaysia and Asian countries, in better understanding their clients. Besides, it also has implications on how more culturally relevant financial education content could further enhance the effectiveness of financial decision-making in general